Multiple gene sequence analysis using genes of the bacterial DNA repair pathway - Miguel Rotelok Neto; Carolina Weigert Galvão; Leonardo Magalhães Cruz; Dieval Guizelini; Leilane Caline Silva; Jarem Raul Garcia; Rafael Mazer Etto (Brazilian Archives of Biology and Technology, 2015)
The ability to recognize and repair abnormal DNA structures is common to all forms of life. Physiological studies and genomic sequencing of a variety of bacterial species have identified an incredible diversity of DNA repair pathways. Despite the amount of available genes in public database, the usual method to place genomes in a taxonomic context is based mainly on the 16S rRNA or housekeeping genes. Thus, the relationships among genomes remain poorly understood. In this work, an approach of multiple gene sequence analysis based on genes of DNA repair pathway was used to compare bacterial genomes. Housekeeping and DNA repair genes were searched in 872 completely sequenced bacterial genomes. Seven DNA repair and housekeeping genes from distinct metabolic pathways were selected, aligned, edited and concatenated head-to-tail to form a super-gene. Results showed that the multiple gene sequence analysis using DNA repair genes had better resolution at class level than the housekeeping genes. As housekeeping genes, the DNA repair genes were advantageous to separate bacterial groups at low taxonomic levels and also sensitive to genes derived from horizontal transfer.